Targeting the Epigenome in Lung Cancer: Expanding Approaches to Epigenetic Therapy - Jakopovic, Marko; Thomas, Anish; Balasubramaniam, Sanjeeve; Schrump, David; Giaccone, Giuseppe; Bates, Susan E. (Frontiers in Oncology, 2013)
Epigenetic aberrations offer dynamic and reversible targets for cancer therapy; increasingly, alteration via overexpression, mutation, or rearrangement is found in genes that control the epigenome. Such alterations suggest a fundamental role in carcinogenesis. Here, we consider three epigenetic mechanisms: DNA methylation, histone tail modification and noncoding, microRNA regulation. Evidence for each of these in lung cancer origin or progression has been gathered, along with evidence that epigenetic alterations might be useful in early detection. DNA hypermethylation of tumor suppressor promoters has been observed, along with global hypomethylation and hypoacetylation, suggesting an important role for tumor suppressor gene silencing. These features have been linked as prognostic markers with poor outcome in lung cancer. Several lines of evidence have also suggested a role for miRNA in carcinogenesis and in outcome. Cigarette smoke downregulates miR-487b, which targets both RAS and MYC; RAS is also a target of miR-let-7, again downregulated in lung cancer. Together the evidence implicates epigenetic aberration in lung cancer and suggests that targeting these aberrations should be carefully explored. To date, DNA methyltransferase and histone deacetylase inhibitors have had minimal clinical activity. Explanations include the possibility that the agents are not sufficiently potent to invoke epigenetic reversion to a more normal state; that insufficient time elapses in most clinical trials to observe true epigenetic reversion; and that doses often used may provoke off-target effects such as DNA damage that prevent epigenetic reversion. Combinations of epigenetic therapies may address those problems. When epigenetic agents are used in combination with chemotherapy or targeted therapy it is hoped that downstream biological effects will provoke synergistic cytotoxicity. This review evaluates the challenges of exploiting the epigenome in the treatment of lung cancer.